Український літературний постмодерн як предмет обговорення в науковій періодиці - Сахарчук, Наталія Юріївна (Східноєвропейський національний університет імені Лесі Українки, 2013)
Статтю присвячено розкриттю проблеми постмодернізму в українській літературній науці. Схарактери-зовано етапи й особливості дискусійного обговорення постмодерну в періодиці від початку його розгляду в 1991 р. до найновіших публікацій. Наголошено на національних особливостях українського постмодерну та його місці у світовому контексті. This article is devoted to the problem of postmodernism in the Ukrainian literary. The basic publications in periodicals are analyzed. The stages and features of discussion about postmodern consideration from the beginning in 1991 to the latest publications are considered. Highlighted the main features of postmodernism in Ukrainian literature. The Ukrainian national characteristics of postmodernism and its place in world literary discourse are outlined. Initially researchers noted a through irony in postmodern art world and his eclectic pluralism. An outstanding feature of Ukrainian postmodern is its resistance to the totalitarian past. Features of Ukrainian postmodern and its proximity to modernism provides that it is built on the grounds of provocation more than satiety public. Article's attached bibliography of 22 items, which is not intended to be exhaustive because of the limited volume of the article, but can serve as a starting material for the study of Ukrainian postmodern literature.
Keywords: постмоденрнізм; постмодерний світогляд; стан постмодерну; дискусія; рецепція